2007 IEEE 13th International Symposium on High Performance Computer Architecture 2007
DOI: 10.1109/hpca.2007.346186
|View full text |Cite
|
Sign up to set email alerts
|

Improving Branch Prediction and Predicated Execution in Out-of-Order Processors

Abstract: If-conversion is a compiler technique that reduces the misprediction penalties caused by hard-to-predict branches, transforming control dependencies into data dependencies. Although it is globally beneficial, it has a negative side-effect because the removal of branches eliminates useful correlation information necessary for conventional branch predictors. The remaining branches may become harder to predict. However; in predicated ISAs with a compare-branch model, the correlation information not only resides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The register stack engine have been replaced by our scheme. The microarchitec- ture features predicate prediction [17]. Load-store queues, as well as the data and control speculation mechanisms defined in IA64, are also modeled and integrated in the memory disambiguation subsystem.…”
Section: Methodsmentioning
confidence: 99%
“…The register stack engine have been replaced by our scheme. The microarchitec- ture features predicate prediction [17]. Load-store queues, as well as the data and control speculation mechanisms defined in IA64, are also modeled and integrated in the memory disambiguation subsystem.…”
Section: Methodsmentioning
confidence: 99%
“…The predicate prediction mechanisms in the literature [4,16,13] only focus on lightly predicated code, in which dependent chains of predicates do not exist. IPP proposed in this paper, conversely, performs both branch and predicate prediction across large and heavily predicated hyperblocks, where chains of dependent predicates exist.…”
Section: Related Work and Generalitymentioning
confidence: 99%
“…Unlike out-of-order designs that use predicates to avoid hard-topredict branches [4,16], EDGE architectures employ predicates to build large instruction blocks to reduce fetch bottlenecks. The combination of speculative block-based execution and predication within blocks in EDGE architectures moves branch prediction off of the critical path and alleviates the fetch bandwidth bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a nearly optimal performance speedup of 2% of ideal speedup. A compilation framework [1] is presented that allows a compiler to maximize the benefits of prediction. Steve Carr (1996) [15] shown how the weakness of traditional heuristics are exploited.…”
Section: Related Workmentioning
confidence: 99%
“…It has been observed that ILP is greatly forced by branch instructions. Also it has been observed that branch prediction is employed with speculative execution [1]. However, inevitable branch misprediction compromises such a remedy.…”
Section: Introductionmentioning
confidence: 99%